PERAN PEKERJA SOSIAL DALAM PELAYANAN SOSIAL BAGI PMKS YANG TERDAMPAK PSBB DI GOR TANAH ABANG JAKARTA PUSAT - Dewi Kartikawati (GoAcademica Research dan Publishing, 2020)
This study aims to determine the implementation of social services for PMKS who are affected by PSBB at the Tengsin Sports Hall, Central Jakarta, and the role of social workers in social services for PMKS after the imposition of large-scale social restrictions (PSBB) at the Karet Tengsin Sports Hall, DKI Jakarta. This research uses a qualitative approach with descriptive methods. The subjects of this study were social workers who served at the Tengsin Rubber Sports Center, Central Jakarta. Data collection was carried out using observation, interview, and documentation techniques. The results showed that the implementation of services for PMKS was carried out through four stages, namely outreach, health checks, assessment and provision of advanced social services according to PMKS needs. The roles of social workers in social services for PMKS affected by the PSBB include, among others, as advocates, counselors, mediators, educators, case managers, facilitators and experts, namely experts in helping determine services according to client needs. Supporting factors for social workers in carrying out their roles are a sense of responsibility as humanitarian workers, both support from the Ministry of Social institutions and the DKI Jakarta Provincial Social Service. The inhibiting factors in carrying out the role of social workers are the concern of contracting co-19, the unpreparedness of service institutions in accepting clients.